Development of physical qualities of athletes aged 9-11 (Bangladesh Journal of Medical Science, 2024)
Background: Great importance is paid to the physical development of school children, the positive influence of physical culture for the growth and development of children has been proven. At the same time, indicators in sports schools are falling due to insufficient development of physical qualities. The problem requires studying and improving the training process of athletes.The aim of the study: To increase the effectiveness of the training process of athletes aged 9-11 years due to the development of certain motor qualities.Study design: Pedagogical experiment.Research methods: The pedagogical experiment was conducted on the basis of the Olympic Reserve School number 1 (Kirov, Russia) from August to November 2022. The study involved children aged 9-11 years. 2 groups were formed: experimental and control consisting of 25 boys each. Classes were held 3 times a week. Children from the control group were engaged in the usual program, and children from the experimental group performed exercises to develop physical qualities. The complex was used for 10 weeks. Tests that were used in the study: Long jump from a place, Shuttle run 3 x 10m, Squats for 30 seconds, Hand strength, Leaning forward from a sitting position.Results: After the study, the experimental group was ahead of the control group in almost all indicators. In the long jump test, the difference between the experimental and control groups was 2.3cm (P